GP73-mediated secretion of PKM2 and GP73 promotes angiogenesis and M2-like macrophage polarization in hepatocellular carcinoma - Shujie Wang; Tongjia Zhang; Yue Zhou; Zitao Jiao; Kejia Lu; Xinyi Liu; Wei Jiang; Zhe Yang; Hui Li; Xiaowei Zhang (Cell Death and Disease)
Abstract Hepatocellular carcinoma (HCC) is one of the most common malignant tumors. Abnormally high expression of Golgi protein 73 (GP73) and pyruvate kinase M2 (PKM2) is intimately associated with HCC progression. However, as secreted proteins, the role of their extracellular secretions in HCC progression remains unclear. Here, we demonstrated that the expression of extracellular GP73 was positively correlated with extracellular PKM2. GP73 interacted with PKM2 to promote SUMO1 modification of PKM2, which in turn enhanced the interaction of GP73 and PKM2. This process continuously promoted the transfer of PKM2 from the cytoplasm to the membrane in HCC cells, and finally secretion. Extracellular PKM2 and GP73 synergistically promoted angiogenesis and polarization of M2-type macrophages, thereby leading to malignant progression and sorafenib resistance in HCC. Sorafenib combined with shikonin, a specific inhibitor of PKM2, has a strong anti-tumor effect. This study reveals the role of GP73 in enhancing PKM2 and GP73 secretion in promoting HCC progression, providing a theoretical basis and drug targets for HCC therapy.